SURFACE HARDENING OF COMPACTED SNOW BY CONTROLLED SOLAR RADIATION ABSORPTION. - Stehle,Nancy S. (1965)
The snow surfaces of compacted-snow roads and runways often do not have adequate surface hardness and wearing ability for repeated traffic. Laboratory tests were conducted at the Naval Civil Engineering Laboratory to study the increase in surface hardness and wearing ability of compacted snow by melting and refreezing the surface snow through controlled absorption of solar radiation by black plastic on the snow surface. In 6- to 8-hour test exposures, the greatest increase in shear strength in the top 6 inches of the snow, the measure of surface hardness for these tests, occurred at +5F after 6-1/2 hours of exposure to 1.10 Langleys/min, equal to 1.1 gm cal/sq cm/min or 243.3 Btu sq ft/hr. (Author)